KEPENTINGAN JERMAN MENERIMA PERMOHONAN SUAKA PERWIRA MILITER TURKI TAHUN 2016-2017 - Sundari, Oktri; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine the diplomatic relations between Germany in Turkey which caused Germany to accept asylum aplications for Turkish. Then find out why Turkish military offecers apply for asylum in Germany. And also out what interest behind Germany accept asylum aplications for Turkish military. Turkish Military Officers who have been convicted or sought for being considered as rebels who carried out the coup on 15 July 2016. They are accused of being a military faction trying to overthrow Erdogan. Therefore, massives depuration took place in Turkey, and many Turkish citizens fled and sought harborage in other countries.The formulation of the problem from this research is why Germany accepted the asylum application. The purpose of this study is to find out the history of the Turkish military coup and the reason Turkish military officers applied for asylum in Germany. This research uses security theory. Where security is seen as a system into a mutually benefical relationship, where some countries are formed by themselves and so are formed by a competitive and fierce anarchy environment. This study also uses qualitative methods that are descriptive analitical, recapitulating the data recorder not as numbers.Germany has an interest behind its attitude to accepting harborage applications for Turkish military officers. Germany did this mainly because it wanted to maintain the stability of its regional security after its country was accused of not being able to fulfill the NATO mission. Germany does not arbitrarily accept harborage applications for Turkish military officers, he mostly accepts harborage applications that have diplomatic passports and those with a military background to be easily placed in NATO bases in Germany. Moreover Germany and Turkey have a bad relationship in recent years due to several reasons, even though both are NATO partners. Therefore, Germany accepts applications for Turkish military harborage which holds a diplomatic passport and is assigned to the NATO military base in Germany.Keywords: Interest, Military Officer, Asylum